2002
DOI: 10.1177/154405910208101011
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in the Response of the Mandible to Orthopedic Force

Abstract: Bone and cartilage metabolism is known to be more active during rest than during periods of activity. The purpose of this study was to examine the hypothesis that mandibular retractive force could be more effective when applied to rats during rest. Mandibular retractive force caused a considerable reduction in the condylar length in experimental groups, and the magnitude of this reduction was greater in the Light-period (08:00-20:00) group than in the Dark-period (20:00-08:00) group. The differentiation and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…The anesthetic procedure precluded a higher frequency of data collection points in the current biolumines-is accelerated at resting periods (Igarashi et al, 1998;Miyoshi et al, 2001;Yamada et al, 2002). Our results could provide support for this approach.…”
Section: Discussionsupporting
confidence: 70%
“…The anesthetic procedure precluded a higher frequency of data collection points in the current biolumines-is accelerated at resting periods (Igarashi et al, 1998;Miyoshi et al, 2001;Yamada et al, 2002). Our results could provide support for this approach.…”
Section: Discussionsupporting
confidence: 70%
“…However, further studies are needed to address this point. Moreover, patients might benefit from a nocturnal use of the appliance because of the more active bone turnover and the reported growth‐promoting effect of functional type orthopaedic appliance during rest .…”
Section: Discussionmentioning
confidence: 99%
“…(29,30) In a rat mandibular model, retractive forces shortening bone had stronger inhibitory effects on chondrocyte differentiation and proliferation during the daylight hours rather than at night. (31) Additional publications have indicated that the diurnal variation in bone resorption may be related to the release of PTH. (32)(33)(34)(35)(36)(37)(38)(39) Genes encoding enzymes from multiple metabolic path- ways display an oscillatory expression profile in calvarial bone; these account for 26.2% of the genes represented on the microarray (5956 of 22,690).…”
Section: Discussionmentioning
confidence: 99%
“…(15)(16)(17)(18)(19)(20) Our transcriptomic analyses have shown that at least 15% or more of adipose tissue genes display a circadian expression profile. (15,16) In light of the extensive studies supporting the role of circadian mechanisms in bone metabolism, (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) we applied a combined quantitative RT-PCR (qRT-PCR) and Affymetrix microarray approach to examine the hypothesis that gene expression of multiple metabolic pathways in murine calvarial bone undergoes circadian oscillation. Because the mRNA levels of Bmal1, Clock, Cry, Dbp, Npas2, Per, Rev-erb␣, and Rev-erb ␤ displayed a robust and characteristic circadian rhythm in adipose tissues and liver, we focused our initial attention to their expression in calvarial bone.…”
Section: Introductionmentioning
confidence: 99%